Beyond Classic Anastomoses Training Models: Overview of Aneurysm Creation in Rodent Vessel Model - García Feijoo, Pablo; Carceller, Fernando; Isla Guerrero, Alberto; Sáez-Alegre, Miguel; Gandía González, Maria Luisa (Frontiers in Surgery, 2022)
Nowadays, due to the decline in the number of microsurgical clippings for cerebral aneurysms and revascularization procedures, young neurosurgeons have fewer opportunities to participate and train on this type of surgery. Vascular neurosurgery is a demanding subspecialty that requires skills only acquired with technical experience. This background pushes the new generations to be ready for such challenging cases by training hard on different available models, such as synthetic tubes, chicken wings, or placenta vessels. Although many training models for vascular neurosurgery have been described worldwide, one of the best ones is the rodent vessels model. It offers pulsation, coagulation, and real blood flow conditions in a physiologic atmosphere that mimics perfectly the intracranial human vessels environment, especially in terms of size. However, the current governmental different regulations about the use of living animals in medical experimentation and the social awareness, as well as the lack of financial support make starting with that kind of training more difficult. In this review, we describe the tools and techniques as basic steps for young neurosurgeons vascular microsurgery training by using rodent models, that provide an accurate copy of brain vessels environment under stable conditions. The initial three classical known microanastomoses for neurosurgeons are end-to-end, end-to-side, and side-to-side, but in literature, there are described other more complex exercises for training and investigation, such as aneurysm models. Although there is still little available data, we aim to summarize and discuss aneurysm´s training models and review the current literature on the subject and its applications, including a detailed description of the techniques.